Profile, correlation, and regression of erythrocyte index in Indonesian local fat-tailed sheep at pregnancy periods various until lactation - Mudawamah Mudawamah; Anggita A.; Lestari M.W.; Afroni M.Y.; Ciptadi G.; Oktanella Y. (BIO Web of Conferences)
Indonesian Local Fat-Tailed sheep called Sapudi are very adaptive to rural farming conditions. This study aimed to analyze the erythrocyte index in Sapudi ewes at various periods of pregnancy until lactation as basic information for breeding ewes. This research method was a case study with sampling criteria of physically healthy ewes and three periods of pregnancy, including early pregnancy (EP), mid-pregnancy (MP), late pregnancy (LP), and lactating ewes (LT). The status of non-pregnant ewes (NP) was used as a control. Data analysis used statistics descriptive of the IBM SPSS 19 program. The variables observed were MCV (Mean Corpuscular Volume ), MCH (Mean Corpuscular Hemoglobine), and MCHC (Mean Corpuscular Hemoglobine). The results showed that the profile of the erythrocyte index tended to differ in each period from pregnancy, lactation, and control. Statistically, the erythrocyte index was significantly different (p <0.05) only in the MCHC variable; the correlation value and regression significance of MCHC with MCH and MCV were 0.99 and 0.44, while the correlation of MCV and MCH was 0.58. This study concluded that the erythrocyte index in MCHC significantly increased by 6.46% in the EP phase and tended to decrease in the MP, LP, and LT phases by 8.02%, 5.41%, and 7.1% compared to the control (NP). A positive correlation of MCHC and MCH with the regression equation y = 4.40 + 2.05X. The study recommended that the breeding management of the sheep should be divided into three minimums: non-pregnant ewes, early pregnant ewes, and middle pregnant until lactation ewes.